PENGARUH DISKON DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN OLEH KONSUMEN HOUSE OF SMITH DI KOTA BANJARMASIN - Gusti M. Ananda Fitriyandi; Nurul Wahyuni; M. Hasanur Arifin (Smart Business Journal (SBJ), 2023)
This research aims to find out and test the significant effect partially or simultaneously Discount and Product Quality on Purchasing Decisions by Consumers At The House Of Smith In The City Of Banjarmasin. This research method have been used a quantitative approach with the type of research used is explanatory research. The type of research is associative research. The study population is the entire consumer house of Smith whose exactness is not known for certain. The number of salmpels in this study was as much as 75 respondents from House of Smith Banjarmasin customers with Purposive sampling technique. The research instrument used a questionnaire. Data analysis have used multiple linear regression analysis, data collection technique F test and T test. The results showed that there was an effect of discount on purchasing decisions at the House of Smith Banjarmasin with the results of the t test that t (count) = 6.784 > t (table) = 1.674 with a sig level of 0.000 < 0.05. There is an effect of product quality on purchasing decisions at the House of Smith Banjarmasin with the results of the t test that t(count) = 14,989> t(table) = 1,674 with a sig level of 0.000 < 0.05. There is an effect of discount and product quality on purchasing decisions by consumers at the House of Smith in Banjarmasin from the test results F (table) = 3.18 < F (count) = 132.452 with a sig level of 0.000 < 0.05.